Behaviour and performance of new issues in Malaysia - Othman Yong, (Penerbit Universiti Kebangsaan Malaysia, 1992)
This study looks at the behaviour and performance of new issues in Malaysia from 1983 to 1988. The results show that the average return, based on the difference between the first day closing price and the offer price , is approximately 167 percent. It is also found that the new issues are overwhelmingly oversubscribed. The returns after the first day and up to one year normally decline, eventhough they are not significantly different from the returns received on the first day of trading. Furthermore, the performance of new issues is quite independent of the ups and downs of the market.